Local Marriage System of Boti Community Depicted Through its Speech Ritual (e-Journal of Linguistics, 2019)
Marriage system in the indigenous trust describes the relationship of supernaturaleffect on family kinship in the community. Such the relevance is the primary identifier and theidentity of the diversity of the Indonesian nation. It is inevitable that a cultureas a pillar ofdiversity is a buffer for entering the era of multicultural and globalization. Values of Humanist isthe power of social relation among individuals in the community groups. This paper describesthe characteristic of marriage in society of Boti in East Nusa Tenggara who hold the originaltrust Halaika.The results shows behaviors that indicate homage to supernatural of Uis Pah (Rulerof the Earth), Uis Oe (Ruler of Water) and Uis Neno (Ruler of Heaven) in a series of marriagesthat is rich of value and meaning.
Keywords: Halaika; Uis Neno; Uis Pah; Uis Oe